Export Potential of Superior Agricultural Commodities in West Sulawesi, Indonesia - Padassejati,; Asrul, Laode; Arsyad, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
The acceleration of the export development of Indonesian agricultural products has fluctuated and the export value of West Sulawesi has increased. This study aims to identify the superior agricultural commodities and export potential of the superior agricultural commodities of West Sulawesi Province. The research used time series data (2013-2018) from the Indonesian Central Bureau of Statistics. The research employed Location Quotient and Klassen Typology Analysis. The results show that the superior agricultural commodities of West Sulawesi are corn (LQ=1.479) for food crops, durian (1.507), langsat (6,523) for horticultural crops, oil palm (1.409), coconut (1,729), coffee (1,029) and cocoa (12,459) for estate crops. The export potential of the leading commodities of West Sulawesi with Klassen typology analysis, namely oil palm (potential for advanced and fast growing exports), coconut, langsat, cocoa, and coffee (potential for developingexports), while corn and durian (potential for advanced but slow growing).